Calculation of Android-Based Zakat on Assets and Profession Zakat - Desiana Mirtasari; Herny Februariyanti; Andi Harpepen (Jurnal Multidisiplin Dehasen (MUDE), 2023)
The ease of the android operating system based on open source, android becomes easy and free to develop. One of them is the use of applications on android-based smartphones related to the fulfillment of obligations on special assets, namely the calculation of zakat. Android-based zakat calculation application is an application that is applied to android smartphones which can help Muslims in calculating zakat that must be issued according to the rules of Allah and His Rosul which can be used anytime, anywhere, and by anyone, besides that this application is also equipped with a zakat alarm feature that can be a reference reminder time in paying zakat on time. The system development method used in making this application is the prototype method. This zakat calculation application is made using java as a programming language with Android Studio as an Integrated Development Environment (IDE). This application uses the calculation formula for property zakat and professional zakat which is applied to the program coding that will calculate the amount of property zakat and professional zakat that must be paid by Muslims. This zakat calculation application can help Muslims in calculating property zakat and professional zakat that must be issued and with the zakat alarm feature can be used as a reminder time reference in paying zakat on time.